Lecture notes on human physiology - Bray, John J; Ed. Cragg, Patricia A; Ed (Blackwell Scientific Publications, 1986)
The eminent team of authors and editors provides a comprehensive introduction to human physiology for undergraduate students of medicine and other health sciences (dentistry, pharmacy, physical education and nutrition) who are taking physiology for the first time.